(untitled) (Torani Journal of Fisheries and Marine Science, 2022)
This study aims to analyze the level of operational perfomance the fishing port clas PPI Lappa of Sinjai Regency. The research method used in a case study with the aspects studied include the provision of facilities used in PPI Lappa operational activities. Data were analyzed descriptively using the scoring method and operational performance appraisal table. The performance assessment is obtained by comparing the current condition of PPI Lappa with the provisions in the regulations stipulated of The Ministry of Maratime Affairs and Fisheries No. PER.08/MEN/2012 concerning fishing ports and the decision of the Director General of Capture Fisheries No.432/DPT3/0T.220.D3/I/2008 regarding guidelines for evaluating the performance of fishing port technical implementing units. The results of the study show that the performance of coconut PPI Lappa is 63,6 % or good performance status. Each parameter has a high percentage of weight and value success, includes the number of produnction 960,05%, ship visting frequensy 73,3%, ice service 458,10 %, fuel service ships 175,40%, clean water service 22,05% and the availability of port fasilities such as administration office, national marketing, marketing facilities, canteen, and mosque. The facilities available but not functioning are the guard post. Facilities that are not available, such as industrial facilities, processing facilities, ship repair facilities, supply facilities for engine parts and polyclinics.